Advancing Engineering Students' Technical Writing Skills by Implementing Team-Based Learning Instructional Modules in an Existing Laboratory Curriculum - Shenghua Wu; Shenghua Zha; Julie Estis; Xiaojun Li (MDPI AG, 2022)
Technical writing is a crucial skill for engineering students' effective written communication, which shapes and affects their professional careers. This study designs team-based learning (TBL) instructional modules that are integrated into an existing engineering laboratory curriculum and evaluates their feasibility and effectiveness in improving engineering students' technical writing skills. The data were collected from structured survey questions distributed to student participants and from the instructor's independent evaluation of students' lab reports. The effect of assigning a team leader on students' writing performances was also evaluated. Our results indicated that students who have received TBL modules perceive a greater improvement in their technical writing skills than those who did not. A strong correlation was found between students' perception and the instructor's evaluation of the students' technical writing skills. Assigning a team leader in TBL instructional modules has not played a significant role in improving engineering students' technical writing skills. The same happens with gender. Overall, utilization of TBL instructional modules can advance engineering students' technical writing skills.